Developing a halal compliance behavioural framework: case of the Malaysian poultry firms - Hashim, Husna; Md Saad, Norma; Khalid, Haniza; Laluddin, Hayatullah (Pusat Pengajian Ekonomi, Fakulti Ekonomi dan Pengurusan, Universiti Kebangsaan Malaysia (UKM), 2016)
Halal industry is the fastest growing global business across the world, as such, food companies are expected to enhance their production processes to comply with halal standards and be subjected to monitoring and control by the respective halal authority, either private or public authority. In food economics, literature shows that probability of food risks which are caused by malpractice or non-compliance increases with the profit that can be earned through opportunistic behaviour. Although halal industry is highly regulated and routinely inspected, little is known about compliance behaviour amongst food producers. In this study, a framework of halal compliance is developed based upon the basic theory of crime deterrent, legitimacy, morality and market forces. Using the sample of Malaysian poultry processing firms, the study determines which of the regulatory, morality and market-based factors are most influential in determining their compliance attitude.